Accelerated Repigmentation of Halo Nevus Following Excision: A Case Report - Gobel, Rika Yulizah; Hutabarat, Emma Novauli; Djawad, Khairuddin; Anwar, Anis Irawan; Wahab, Siswanto; Nurdin, Airin; Idrus, Idrianti (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Halo nevus is a benign condition characterized by symmetrical oval-shaped and well-defined hypopigmented patch surrounding melanocytic lesions. Their sizes varies from a few millimeters to centimeters. A “wait and see” approach is usually preferred in most cases of halo nevus. However, the condition can cause severe psychological impact and impair patient’s quality of life, especially when it emerges on prominent areas such as the face. Surgical option can be utilized for removal of melanocytic lesions and accelerate regression of the halo. CASE PRESENTATION: We report a case of a 25-year-old woman with white patches around two moles on her face who was diagnosed as halo nevus. Surgical excision was performed and a 12-week follow-up showed reduction in diameter of the halo nevus. CONCLUSION: Large halo nevus can cause significant esthetic burden that may affect patient’s quality of life. A more invasive approach such as excision of underlying nevus may be used to achieve more rapid results.